Combination of Cultured Epidermal Autograft and Meshed Skin Graft Enables Full-thickness Excision of Giant Congenital Nevus - Chie Kobori, MD; Makoto Hikosaka, MD; Wataru Tsugu, MD; Koki Sakurai, MD; Yukari Nakajima, MD; Hikaru Kono, MD; Akira Kikuchi, MD; Yuki Nakajima, MD; Miho Sumi, MD; Kosuke Kuwahara, MD, PhD; Tsuyoshi Kaneko, MD (Plastic and Reconstructive Surgery, Global Open, 2024)
Summary:. Giant congenital melanocytic nevus (GCMN) is a skin condition characterized by an abnormally dark, noncancerous skin patch. Two main issues with GCMN are aesthetics and malignant transformation. Various methods of treatment are reported, but each method has its own disadvantages, such as risk of recurrence or restriction in the treatable area. We report three cases of GCMN treated with full-thickness excision and immediately covered with cultured epidermal autograft (CEA) combined with split-thickness skin graft (STSG). This is a single-center, single-arm, retrospective report of three cases. The nevus was excised at full skin thickness. Meshed STSG taken from scalp was grafted to the defect, and CEA was grafted over simultaneously. Two weeks later, CEA was applied again as a booster. The same procedures were performed until all nevi were excised. In all cases, nearly complete epithelialization was achieved at several weeks after operation. The reconstructed skin was elastic, and there was no persistent joint contracture. Vancouver Scar Scale score was 4–8. Mesh-like appearance was observed. A hypertrophic scar appeared in the area without meshed STSG. An intractable keloid was observed in one patient. No recurrence of the nevus was observed during the follow-up period. The donor site scar on the scalp was well hidden by the hair. Our method enables full-thickness resection and reconstruction of a wider area in a single operation while improving the take rate of CEA, with reasonable degree of scarring compared with conventional methods.